2010
DOI: 10.1007/s10495-010-0498-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β induces ER stress in a JNK dependent manner that determines cell death in human pancreatic epithelial MIA PaCa-2 cells

Abstract: The proinflammatory cytokine, IL-1beta (Interleukin-1beta) is a significant determinant of pancreatic apoptosis and cell death that are common characteristics during diabetes. Using human derived pancreatic MIA PaCa-2 cells, we describe one of the underlying molecular mechanisms behind this observation. Incubation of these cells with IL-1beta at doses from 0.5 to 3.0 ng/ml caused significant cell death at 36 h. This was accompanied with marked increases in JNK and p38 phosphorylation together with increased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 60 publications
(100 reference statements)
3
46
0
Order By: Relevance
“…It is well established that activation of IRE1 can lead to the phosphorylation of JNK, which plays critical roles in pro-apoptotic pathways (Tabas and Ron, 2011). Meanwhile, research also found that JNK signaling can reciprocally regulate ER stress through an unidentified mechanism (Li et al, 2013; Verma and Datta 2010). In our study, we demonstrated that blocking JNK activity using the inhibitor SP600125 could partially attenuate the increase in CHOP and recover the cell viability, further supported the complicated role of JNK signaling in ER stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that activation of IRE1 can lead to the phosphorylation of JNK, which plays critical roles in pro-apoptotic pathways (Tabas and Ron, 2011). Meanwhile, research also found that JNK signaling can reciprocally regulate ER stress through an unidentified mechanism (Li et al, 2013; Verma and Datta 2010). In our study, we demonstrated that blocking JNK activity using the inhibitor SP600125 could partially attenuate the increase in CHOP and recover the cell viability, further supported the complicated role of JNK signaling in ER stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chan et al (43) showed that proinflammatory cytokines induce ER stress as increased phosphorylation of PERK and eIF2␣, up-regulating ATF4 expression in islets cells. IL-1␤ induces ER stress through JNK, which determines pancreatic cell death (44). Therefore, IL-1␤-induced translational efficiency of ATF5 mRNA could be regulated by PERK-mediated eIF2␣ phosphorylation in a JNK-dependent manner in liver and pancreatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Second, IL-1β can efficiently evoke the expression of other inflammatory mediators through IL-1R signaling and provides the basis for a self-amplifying cytokine network (Arend et al, 2008 IL-18, and IL-33 families of cytokines). Third, IL-1β induces cell stress, such as ER stress and oxidative stress, both of which have been tightly linked to the pathogenesis of T2D (Cardozo et al, 2005; Verma and Datta, 2010). These findings highlight IL-1β as a potential therapeutic target for the treatment of T2D and small-scale studies employing recombinant IL-1 receptor antagonist (IL-1Ra) provide encouraging data in the treatment of T2D (Larsen et al, 2007).…”
Section: Inflammasome and Type 2 Diabetesmentioning
confidence: 99%